2021
DOI: 10.51791/njap.v48i4.3008
|View full text |Cite
|
Sign up to set email alerts
|

The role of selenium in ameliorating the impact of heat stress on growth, hormones, minerals and tibia measurements of broiler chickens

Abstract: The study was conducted to investigate the potent capacity of selenium to curtail the adverse  effects of heat stress in broiler chickens. A total of 256, day old Cobb 500 broiler chicks were  randomly allotted to four experimental treatments (0, 0.1, 0.2 and 0.3 mgSe/kg), with four  replicates in a completely randomized design. Initial weight, daily feed intake, daily weight  gain, final weight, feed conversion ratio, daily water intake, feed cost/kg gain, mortality,  serum cortisol and thyroxine levels, calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…This is due to the birds' successful efforts to re-establish homeostasis and mitigate the effects of dexamethasone. While this is contrary to the findings of Ndubuisi et al (2021), it is in agreement with Khan et al (2014) who reported a decrease in body temperature as a response to antioxidants in broiler chickens. An increase in respiratory rate and a decrease in body temperature also validates successful heat loss by panting employed by the birds to combat heat stress.…”
Section: Thermoregulatory Indicessupporting
confidence: 90%
“…This is due to the birds' successful efforts to re-establish homeostasis and mitigate the effects of dexamethasone. While this is contrary to the findings of Ndubuisi et al (2021), it is in agreement with Khan et al (2014) who reported a decrease in body temperature as a response to antioxidants in broiler chickens. An increase in respiratory rate and a decrease in body temperature also validates successful heat loss by panting employed by the birds to combat heat stress.…”
Section: Thermoregulatory Indicessupporting
confidence: 90%
“…Cortisol, the most important glucocorticoid, has been found to be immunosuppressive, thus inhibiting the production and actions of antibodies, the lymphocyte function and the leucocyte population [38]. A few studies have already reported the beneficial effect of Se on the plasma cortisol level of heat-stressed broilers [39]. However, to the best of our knowledge, this is the first study that has shown a significant difference between inorganic and organic forms of Se.…”
Section: Discussionmentioning
confidence: 81%
“…Thus, maintaining an optimal Se status in the body helps to effectively regulate the synthesis of thyroid hormones and restores body homeostasis, particularly under specific physiological conditions and under pathological or environmental stimuli, when the synthesis and regulation of thyroid hormones may be impaired [7,10]. As the release of cortisol into the circulatory system is a classical response to stress [39,40], and thyroid hormones (T3) are the principal determinants of the metabolic rate and heat production of a body [30,36], our observations seem to indicate that organic forms of Se, and OH-SeMet, in particular, could help animals to better adapt to such conditions.…”
Section: Discussionmentioning
confidence: 99%
“…However, in this study none of the bone morphometry and bone mineralization parameters were affected by supplementation of different levels of selenium and vitamin E in the diet of broiler chicken. On similar lines, the selenium supplementation was reported to have no influence on the calcium, phosphorus, and ash content of tibia bones (Ndubuisi et al 2021), however, on contrary these authors reported increased bone weight and length in broiler chicken. Similarly, selenium supplementation had no effect on the tibia bone weight but resulted in higher bone calcium percentage which indicates improved bone mineralization in response to selenium supplementation (Attia et al 2010).…”
Section: Letters In Animal Biology 01(2): 21 -25mentioning
confidence: 88%